Approaches to the Application of Corporate Governance Regulations - Ekundayo, Veronica Ngozi; Sodipo, Bankole (Society & Sustainability, 2022)
To enhance good corporate governance practices, companies, as well as countries, have adopted and promulgated regulations and codes of best practices. To implement these regulations and practices, regulators adopt various approaches which can be broadly classified into voluntary, mandatory, and hybrid. This study examined the aforementioned approaches with particular attention to their strengths and weaknesses. The study employed a qualitative methodology using the doctrinal research method. The doctrinal method relied on primary and secondary sources. The primary sources included legislations and corporate governance codes while the secondary sources included books, e-books, journals, and articles. This methodology was deployed in appraising, interpreting, and applying these various sources of material used in the study. The study found that there are different variations and modifications to the approaches to the application of corporate governance regulations and practices. To facilitate a more efficient and effective corporate governance regime, a combination of the rule-based and principle-based approaches to the application of corporate governance is required.